Where is the father? Challenges and solutions to the inclusion of fathers in child feeding and nutrition research - Andreia F. Moura; Kaat Philippe (BMC, 2023)
Abstract Despite an increasing acknowledgement of fathers' involvement in and impact on children's lives, fathers remain underrepresented in child feeding and childhood obesity prevention research, interventions, and actions. Built on our own experiences with conducting research with fathers and recent evidence on this topic, this Research in Practice article has three aims. It will first substantiate the importance of including and studying fathers in the field of child feeding and childhood obesity prevention based on recent study results. Secondly, the article will present and discuss barriers to fathers' inclusion and participation (why isn't it happening?), among other issues, by drawing on sociological and gender ideological insights. Finally, it will provide recommendations and suggestions related to recruitment, focus and methods that can facilitate fathers' involvement in future research, interventions, and practice. Taken together, this article aims to provide tools for giving fathers a voice in the field of child nutrition and by doing so, to decrease maternal-only "burden" of care. We hope our experiences and theoretical reflections will inspire and support researchers and practitioners to be as successful as possible in the realm of family care.